2015
DOI: 10.1289/ehp.1408254
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Mortality in Seven Million Adults: The Dutch Environmental Longitudinal Study (DUELS)

Abstract: BackgroundLong-term exposure to air pollution has been associated with mortality in urban cohort studies. Few studies have investigated this association in large-scale population registries, including non-urban populations.ObjectivesThe aim of the study was to evaluate the associations between long-term exposure to air pollution and nonaccidental and cause-specific mortality in the Netherlands based on existing national databases.MethodsWe used existing Dutch national databases on mortality, individual charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
141
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(154 citation statements)
references
References 32 publications
10
141
1
2
Order By: Relevance
“…After determining the PM 2.5 concentrations at the sampled points, data truncation is necessary because some predicted values may differ substantially from the true values (i.e., the predicted values are outside the predicted data range). The data range is set as 60% of the observed minimum value to 120% of the observed maximum value for each monitoring site (which is applied in [39,45]). …”
Section: Self-adaptive Revised Lur Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…After determining the PM 2.5 concentrations at the sampled points, data truncation is necessary because some predicted values may differ substantially from the true values (i.e., the predicted values are outside the predicted data range). The data range is set as 60% of the observed minimum value to 120% of the observed maximum value for each monitoring site (which is applied in [39,45]). …”
Section: Self-adaptive Revised Lur Modelmentioning
confidence: 99%
“…However, the most commonly used predictor variables in LUR models are land use (green land, residential land, and construction land), transportation, water, and terrain data. In addition, researchers [39] have applied POI data, such as restaurant data, crossroads, bus stops, etc. Third, most studies have used linear regressions as prediction models because they are easy to implement.…”
Section: Self-adaptive Revised Lur Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have shown positive associations between air pollutants such as particulate matter of aerodynamic diameter less than 10 µm (PM 10 ), nitrogen dioxide (NO 2 ), sulphur dioxide (SO 2 ), ozone (O 3 ) and carbon monoxide (CO) and adverse health outcomes (Goldberg et al, 2013;Crouse et al, 2015;Fischer et al, 2015;Liu et al, 2015;Wong et al, 2015;Yorifuji et al, 2016). Many studies have been conducted to assess the health impacts of air pollution in various cities of the world (Boldo et al, 2006;Fattore et al, 2011;Orru et al, 2012;Allen et al, 2013), including Iranian cities (Naddafi et al, 2012a;Gholampour et al, 2014;Ghozikali et al, 2016;Mohammadi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…are determined to be associated with different health outcomes. Epidemiological studies have been conducted in various countries to investigate this relationship precisely (4)(5)(6)(7)(8). Particulate matter of 2.5 micrometers or smaller (PM 2.5 ) is a part of particulate matter, but is able to enter the alveolar lung region, a place to exchange the blood.…”
Section: Introductionmentioning
confidence: 99%